Respuesta :

ANSWER

[tex]P(B \: and \: C) = \frac{1}{6}[/tex]


EXPLANATION

Recall that,

[tex]P(A \: and \: B)=P(A) \times P(B)[/tex]

But we were given that,

[tex]P(A)= \frac{1}{8} [/tex]

and

[tex]P(A \: and \: B) = \frac{1}{12} [/tex]


We substitute these values into the above formula to obtain,


[tex] \frac{1}{12} = \frac{1}{8} \times P(B)[/tex]



This implies that,

[tex] \frac{1}{12} \times 8=8 \times \frac{1}{8} \times P(B)[/tex]



This simplifies to,

[tex] P(B) = \frac{8}{12} [/tex]


[tex] P(B) = \frac{2}{3} [/tex]


So we can now find
[tex]P(B \: and \: C).[/tex]



We use the same formula again,

[tex]P(B \: and \: C) = P(B) \times P(C)[/tex]
We substitute the values to get,


[tex]P(B \: and \: C) = \frac{2}{3} \times \frac{1}{4} [/tex]
We multiply out to get,


[tex]P(B \: and \: C) = \frac{1}{6}[/tex]


Answer:

1/6

Step-by-step explanation: